Alcohol Consumption as a Risk Factor for Dementia and Cognitive Decline: Meta-Analysis of Prospective Studies - Anstey, Kaarin J.; Mack, Holly A.; Cherbuin, Nicolas (The American journal of geriatric psychiatry, 2009)
The relationships between alcohol consumption and dementia and cognitive decline were investigated in a systematic review including meta-analyses of 15 prospective studies. Follow-ups ranged from 2 to 8 years. Meta-analyses were conducted on samples including 14,646 participants evaluated for Alzheimer disease (AD), 10,225 participants evaluated for vascular dementia (VaD), and 11,875 followed for any type of dementia (Any dementia). The pooled relative risks (RRs) of AD, VaD, and Any dementia for light to moderate drinkers compared with nondrinkers were 0.72 (95% CI = 0.61–0.86), 0.75 (95% CI = 0.57–0.98), and 0.74 (95% CI = 0.61–0.91), respectively. When the more generally classified “drinkers,” were compared with “nondrinkers,” they had a reduced risk of AD (RR = 0.66, 95% CI = 0.47–0.94) and Any dementia (RR = 0.53, 95% CI = 0.53–0.82) but not cognitive decline. There were not enough data to examine VaD risk among “drinkers.” Those classified as heavy drinkers did not have an increased risk of Any dementia compared with nondrinkers, but this may reflect sampling bias. Our results suggest that alcohol drinkers in late life have reduced risk of dementia. It is unclear whether this reflects selection effects in cohort studies commencing in late life, a protective effect of alcohol consumption throughout adulthood, or a specific benefit of alcohol in late life.